The Secrets of Qur’anic Systems in the Multiplicity of Morphological Formulas of the Same Root - Al-Rabay, Hamoud Bin Hammad (Arts for Linguistic & Literary Studies, 2024)
The research aims to reveal the secrets of the Qur’anic systems in the multiplicity of morphological formulas of the same root, and to know the function of each formula, and the differences and connotations it contains. It is divided into an introduction and two sections, the first section: defining the morphological formula. The second topic: studying the multiplicity of morphological formulas with one root and analyzing them through books of interpretation, Qur’anic sciences, books of readings, language books and dictionaries, and books of grammar and morphology. The research concluded that the multiplicity of morphological formulas of the same root may be due to the Arabs’ expansiveness in their speech, or to indicate emphasis and that the morphological formulas may be multiple and combined at the same time. This is because the Arabs in their speech move from the lowest to the highest, and advance from least to most.